Military Implications of the Russian Federation’s Politics of Expansion - Marek Bodziany; Zbigniew Ściborek (Historia i Polityka, 2019)
The achieved status of coexistence has not been accepted by all states. Russia cannot accept the fact that it has sustained substantial losses, especially in the global dimension, after the collapse of the USSR. Vladimir Putin’s team has been striving to rebuild the power of their country. Russian society, which is accustomed to sacrifices for its homeland, is actively involved in the activities undertaken. Much effort is put into the development of the armaments sector. The structures, command and mobilization condition of the Armed Forces are improved. The Russian Armed Forces is modernized and the percentage of modern equipment is constantly increasing. The Armed Forces of the RF are preparing for any possible armed conflict. Various types of exercise are being performed and frequently maneuvers are carried out in close proximity to the borders of NATO member states. However, it must be hoped that Russia’s leadership remains in the sphere of ‘dreams of power’, though the analysis of question marks emerging in the East should be a kind of basis for conclusions.